APLIKASI KOMPOS PUPUK HIJAU DAN ZPT FLORAVIT TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT (Solanum lycopersicum L) - Al Hadi, Budi; Karnilawati, Karnilawati; Yulianda, Yulianda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
The study aims to determine the effect of application of green manure compost and ZPT floravit to increase the growth and production of tomato plants. The research was carried out in the experimental garden of the Faculty of Agriculture, Jabal Ghafur Sigli University. The materials used were tomato seeds of Servo variety, green manure compost and ZPT Floravit. This study used a factorial randomized block design. The green manure compost factor is, K1:10 tons/ha, K2:20 tons/ha, K3:30 tons/ha and the floravit ZPT concentration factor is Z1:1 ml/liter, Z2:1.5 ml/liter, Z3:3 ml/liter of water. The results showed green manure compost had a significant effect on plant heigh at 35 DAP and the number of branches 45 DAP, no significant effect on plant height 25 and 45 DAP, the number of branches 25 and 35 DAP, fruit weight and fruit weight per plot. The concentration of floraphyte ZPT had no significant effect on plant height, number of branches, weight of fruit planted and weight of fruit per plot. There was an interaction between green manure compost and PGR Floravit on plant height at 35 DAP in the combination treatment (K2Z3).Keywords: tomato, green manure compost, ZPT floravit